Corrosion resistance evaluation of HVOF produced hydroxyapatite and TiO2-hydroxyapatite coatings in hanks' solution - Melero, Hortensia Correas; Sakai, Rafael Toshio; Vignatti, Claudia Abellan; Benedetti, Assis Vicente [UNESP]; Fernández, Javier; Guilemany, Josep Maria; Suegama, Patricia Hatsue (FapUNIFESP (SciELO), 2018)
The electrochemical behavior of HVOF produced hydroxyapatite (HA) and 80HA-20TiO2 coatings were investigated using electrochemical techniques in natural aerated Hanks' solution in the presence and absence of bovine serum albumin (BSA) for 30 days. All samples presented open circuit potential oscillations, which were associated to the porous nature of the coating that allows the electrolyte reaches the substrate causing activation - passivation at the bottom of the pores. The polarization studies indicated that the 80HA-20TiO2 coating was the only one that showed a narrow potential passive region from around -0.4 V to 0 V in the presence and absence of BSA, indicating the beneficial influence of the addition of TiO2 to the HA coating stability. Our results indicated that BSA in Hanks' solution diminishes the stability of the metallic oxide layer present on the Ti-based alloy accelerating the degrading of hydroxyapatites coatings / substrate interface due to its chelating ability.
Keywords: BSA; HVOF; Hydroxyapatite coating; TiAlV alloy; TiO2-hydroxyapatite coating